2004
DOI: 10.1196/annals.1297.016
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Senescent Heart to Stress: Clinical Therapeutic Strategies and Quest for Mitochondrial Predictors of Biological Age

Abstract: The aging heart has an impaired response to many kinds of stress. In clinical practice, there is a need for senescence-specific therapies to protect against stress and for biochemical markers of senescence to identify those patients most in need of therapy. In isolated rat hearts, in human tissues, and in a clinical trial, we have shown previously that coenzyme Q(10) has the ability to protect the heart against stress especially in senescence. We recently have devised a regimen of therapy to protect the senesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…There were no significant differences detected for plasma Se or GSH-Px between males and females, however there was a trend for males to have lower levels of Se, especially in the 81 years and over age group. It is plausible that lowered Se levels in males may be associated with the higher morbidity and mortality generally reported in elderly males [22].…”
Section: Healthy Controlsmentioning
confidence: 99%
“…There were no significant differences detected for plasma Se or GSH-Px between males and females, however there was a trend for males to have lower levels of Se, especially in the 81 years and over age group. It is plausible that lowered Se levels in males may be associated with the higher morbidity and mortality generally reported in elderly males [22].…”
Section: Healthy Controlsmentioning
confidence: 99%
“…Therefore, some SH reagents may cause the reversible inactivation of the CPR. One of them might be a strong antioxidant -␣ -lipoic acid, a well-known essential cofactor for the metabolism of ␣ -keto acid used as a therapeutic agent in liver, heart and neurological diseases [9,[22][23][24] . Moreover, it was reported that the substance interferes with SH-containing enzymes, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of identifying factors that modify cardiovascular changes [2,[9][10][11], including lifestyle factors, is reinforced by the substantial variability among older persons in the degree to which these cardiovascular changes that accompany aging occur. Treatments targeting structural factors have begun.…”
Section: Resultsmentioning
confidence: 99%
“…Senescent cardiac myocytes are characterized by altered metabolic, ionic, and electrical properties due partly to increased myocyte size, altered membrane composition, reduced capacity to maintain ion homeostasis, reduced Ca 2+ tolerance, increased reactive O 2 species levels in response to a variety of stressors, and reduced adaptive capacity to invoke bischemic preconditioning-likeQ intracellular signal transduction for post-stress survival [5][6][7][8][9].…”
mentioning
confidence: 99%